Lithospheric flexure and rheology determined by climate cycle markers in the Corinth Rift - de Gelder, Gino (Sci Rep, 2019)
Geomorphic strain markers accumulating the effects of many earthquake cycles help to constrain the mechanical behaviour of continental rift systems as well as the related seismic hazards. In the Corinth Rift (Greece), the unique record of onshore and offshore markers of Pleistocene ~100-ka climate cycles provides an outstanding possibility to constrain rift mechanics over a range of timescales. Here we use high-resolution topography to analyse the 3D geometry of a sequence of Pleistocene emerged marine terraces associated with flexural rift-flank uplift. We integrate this onshore dataset with offshore seismic data to provide a synoptic view of the flexural deformation across the rift. This allows us to derive an average slip rate of 4.5–9.0 mm·yr(−1) on the master fault over the past ~610 ka and an uplift/subsidence ratio of 1:1.1–2.4. We reproduce the observed flexure patterns, using 3 and 5-layered lithospheric scale finite element models. Modelling results imply that the observed elastic flexure is produced by coseismic slip along 40–60° planar normal faults in the elastic upper crust, followed by postseismic viscous relaxation occurring within the basal lower crust or upper mantle. We suggest that such a mechanism may typify rapid localised extension of continental lithosphere.